If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(2 + -2x) = -6(x + -1) (2 * 3x + -2x * 3x) = -6(x + -1) (6x + -6x2) = -6(x + -1) Reorder the terms: 6x + -6x2 = -6(-1 + x) 6x + -6x2 = (-1 * -6 + x * -6) 6x + -6x2 = (6 + -6x) Solving 6x + -6x2 = 6 + -6x Solving for variable 'x'. Reorder the terms: -6 + 6x + 6x + -6x2 = 6 + -6x + -6 + 6x Combine like terms: 6x + 6x = 12x -6 + 12x + -6x2 = 6 + -6x + -6 + 6x Reorder the terms: -6 + 12x + -6x2 = 6 + -6 + -6x + 6x Combine like terms: 6 + -6 = 0 -6 + 12x + -6x2 = 0 + -6x + 6x -6 + 12x + -6x2 = -6x + 6x Combine like terms: -6x + 6x = 0 -6 + 12x + -6x2 = 0 Factor out the Greatest Common Factor (GCF), '6'. 6(-1 + 2x + -1x2) = 0 Factor a trinomial. 6((-1 + x)(1 + -1x)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(-1 + x)' equal to zero and attempt to solve: Simplifying -1 + x = 0 Solving -1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + x = 0 + 1 x = 0 + 1 Combine like terms: 0 + 1 = 1 x = 1 Simplifying x = 1Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {1, 1}
| 6x+34=-36 | | -0.7X+5.85=-0.5X+8.25 | | 4(3x-4)=2(3x+1) | | (20x+4)=(6x+4) | | 10.410= | | 3x(2-2x)=-6x(x-1) | | 2w-54=-w+21 | | 7a+4=4a | | 2=5y-3 | | H=16t^2+352t | | 15x-9=3x+2 | | (8x+18)=(6x+4) | | F=1/2gq | | 5-3s=-s-5 | | 3n-21=2n | | 8x+18=6x+4 | | 5+4v=29 | | 8x+2-3=1 | | 3x-1=77 | | 0p+9-11-p=2(2p+4)-3(2p-2) | | 2v+5=4u+13 | | 126=-9(4+r) | | 2p+9=3p-6 | | p-12=34+q | | Y-18=x+5 | | 3p=7(9p+2) | | 3(6x+2)=30 | | 4x-2(x-3)=-9+5x-9 | | 13.3+7u=-4.2 | | 7+5p=6p | | 7+5(2x+3)-9= | | 3x+8x-2=108 |